PVA-graphene-hydroxyapatite electrospun fibres as air-filters. (22nd January 2020) - Mukherjee, Sneha; Kumar, Sharad; Sahu, Ranjan Kumar; Nayar, Suprabha
Abstract: In this study, the feasibility of specially designed multifunctional electrospun fibres to absorb particulate matter 2.5 (PM2.5) is studied. Here, Poly(vinyl)alcohol (PVA) is used as the polymer for electrospinning, along with colloidal graphene (G) containing in situ synthesized hydroxyapatite (HA) nanoparticles. This fibre is in the nanometre range, has good mechanical resistance, is not toxic and can be washed and reused and is biodegradable. A comparison of PVA, PVA-G and PVA-G-HA before and after heat treatment with two commercial masks, by scanning electron microscopy (SEM), shows a difference in the fibre diameter. The smaller the fibre diameter and the more compact the woven fibres, the better is the PM capture, studied using a PM monitor. Post PM capture, the SEM shows a web-like film formation on the fibres and also a distinct colour change. Anti-bacterial studies using two different bacteria, Escherichia coli and Serratia marcescens shows the zone of inhibition comparable to the control antibiotic. The UV absorption of all the fibres is in the 300–400 nm range with PVA-G-HA showing a maximum at 300 nm, an important property for face masks. The conclusion that can be drawn from detailed XPS studies is that the PVA-G-HA is capable of adsorbing toxic and pollutant gases from the mosquito coil which serves as a source of PM 2.5, considerably more than the other fibres studied. Mechanical studies also show PVA-G-HA to be the most stable fibre studied and hence the potential to be used as face masks/ air filters.